A multi-band SIW based antenna for wireless communication. Issue 2 (3rd April 2021) - Vala, Alpesh; Patel, Amit
ABSTRACT: This paper presents the design and development of planar triplexer slot antenna using substrate integrated waveguide (SIW) technology. The proposed antenna is realised using 'Y' shaped slot backed by SIW cavity. SIW cavity is excited by three separate feed lines for resonance at three different frequencies of 5.7 GHz, 6 GHz and 6.4 GHz with unidirectional radiation pattern and gain of 6.26 dBi, 5.87 dBi and 5.19 dBi, respectively. Average isolation of the three ports is better than 24 dB. All the simulations are carried out using high frequency structure simulation (HFSS) software. The proposed antenna is fabricated on RT Duroid 5880substrate and measured results show better performance. The developed antenna is small in size (0.79 λ × 0.78 λ ), simple to fabricate and easy to integrate with planar technology making it suitable for C-band application.